2008
DOI: 10.1097/inf.0b013e31815ac585
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutralizing Antibodies in Protection of American Indian Infants Against Respiratory Syncytial Virus Disease

Abstract: These findings indicate that American Indian infants with high concentrations of maternally derived RSV neutralizing antibodies are protected from RSV hospitalization before 6 months of age. However, these antibodies do not modify the severity of illness once disease has occurred. The basis for elevated rates of RSV disease among American Indian infants cannot be attributed to a failure of maternal RSV neutralizing antibodies to confer protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 18 publications
3
52
0
1
Order By: Relevance
“…[21][22][23] Another study highlighted the poor role of antibody concentration in conditioning the severity of RSV disease because it showed that children with high levels of maternally derived neutralizing antibodies, despite having a reduced risk of infection, have disease with the same severity of children with a low antibody concentration when RSV infection occurs. 4 In this study, it was expected that the lack of an association between viral factors and immune response and the severity of the disease does not influence immune response. However, the small number of children with LRTI involved in the study, the moment of viral load determination and the methods used to identify the virus could be the reason for this result.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[21][22][23] Another study highlighted the poor role of antibody concentration in conditioning the severity of RSV disease because it showed that children with high levels of maternally derived neutralizing antibodies, despite having a reduced risk of infection, have disease with the same severity of children with a low antibody concentration when RSV infection occurs. 4 In this study, it was expected that the lack of an association between viral factors and immune response and the severity of the disease does not influence immune response. However, the small number of children with LRTI involved in the study, the moment of viral load determination and the methods used to identify the virus could be the reason for this result.…”
Section: Discussionmentioning
confidence: 92%
“…3 Previous studies have shown that the neutralizing antibody concentration plays a fundamental role in conditioning susceptibility to RSV disease and its severity. 4 High titres of maternally derived neutralizing antibodies to RSV correlate well with the protection of younger infants, 4 and the administration of polyclonal or humanized monoclonal antibodies against RSV has been associated with a significant reduction in the number of severe cases and hospitalizations from RSV infection in high-risk infants. 5 Active immunization with RSV vaccines could reduce most of the clinical, economic and societal problems strictly related to RSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy populations, RSVspecific IgG transfer from pregnant women to infants is an active process resulting in higher antibody titers in the infant than in the mother (8). Several studies have demonstrated a reduced incidence of RSV disease during the first several months after birth that correlates with higher concentrations of RSV-specific maternal antibody (9)(10)(11)(12). Further, prevention of RSV in the mother resulting in reduced transmission to the infant is another potential benefit of vaccinating pregnant women.…”
mentioning
confidence: 99%
“…Maternally-derived high affinity RSV-specific serum IgG antibody is the best known correlate of protection against infection in infants (Fig 2d) and it is assumed that the relative rarity of severe RSV disease in the first weeks of life is due to virus-specific maternally derived antibody 44,45,[63][64][65][66][67] . However, some of this protection may be indirect, due to reduced rates of maternal infection in those with high levels of antibody.…”
Section: Rsvmentioning
confidence: 99%
“…Nevertheless, severe RSV infection is consistently associated with low levels of pre-existing serum or cord blood RSV antibody 44,45,[63][64][65][66][67] . Infants in the top .…”
Section: Rsvmentioning
confidence: 99%